High Frankia abundance and low diversity of microbial community are associated with nodulation specificity and stability of sea buckthorn root nodule - Liu, Hong; Ni, Bingbing; Duan, Aiguo; He, Caiyun; Zhang, Jianguo (Frontiers in Plant Science, 2024)
Actinorhizal symbioses are gaining attention due to the importance of symbiotic nitrogen fixation in sustainable agriculture. Sea buckthorn (Hippophae L.) is an important actinorhizal plant, yet research on the microbial community and nitrogen cycling in its nodules is limited. In addition, the influence of environmental differences on the microbial community of sea buckthorn nodules and whether there is a single nitrogen-fixing actinomycete species in the nodules are still unknown. We investigated the diversity, community composition, network associations and nitrogen cycling pathways of the microbial communities in the root nodule (RN), nodule surface soil (NS), and bulk soil (BS) of Mongolian sea buckthorn distributed under three distinct ecological conditions in northern China using 16S rRNA gene and metagenomic sequencing. Combined with the data of environmental factors, the effects of environmental differences on different sample types were analyzed. The results showed that plants exerted a clear selective filtering effect on microbiota, resulting in a significant reduction in microbial community diversity and network complexity from BS to NS to RN. Proteobacteria was the most abundant phylum in the microbiomes of BS and NS. While RN was primarily dominated by Actinobacteria, with Frankia sp.EAN1pec serving as the most dominant species. Correlation analysis indicated that the host determined the microbial community composition in RN, independent of the ecological and geographical environmental changes of the sea buckthorn plantations.Nitrogen cycle pathway analyses showed that RN microbial community primarily functions in nitrogen fixation, and Frankia sp. EAN1pec was a major contributor to nitrogen fixation genes in RN. This study provides valuable insights into the effects of eco-geographical environment on the microbial communities of sea buckthorn RN.These findings further prove that the nodulation specificity and stability of sea buckthorn root and Frankia sp. EAN1pec may be the result of their long-term coevolution.